Alternate synthesis of enantiomerically pure levetiracetam (Keppra (R)) - Mujahid, Mohammad; Mujumdar, P.; Sasikumar, M.; Kunte, S. S.; Muthukrishnan, Murugan (Tetrahedron-Asymmetry, 2012)
A simple and efficient synthesis of levetiracetam has been achieved with high enantiopurity (>99%) starting from commercially available benzyl glycidyl ether. The method is amenable for industrial scale-up. (C) 2012 Elsevier Ltd. All rights reserved.